Integrating Flexible Electrochemical Sensor into Microfluidic Chip for Simulating and Monitoring Vascular Mechanotransduction. Issue 9 (12th August 2019) - Jin, Zi‐He; Liu, Yan‐Ling; Fan, Wen‐Ting; Huang, Wei‐Hua
Abstract: As an interface between the blood flow and vessel wall, endothelial cells (ECs) are exposed to hemodynamic forces, and the biochemical molecules released from ECs–blood flow interaction are important determinants of vascular homeostasis. Versatile microfluidic chips have been designed to simulate the biological and physiological parameters of the human vascular system, but in situ and real‐time monitoring of the mechanical force–triggered signals during vascular mechanotransduction still remains a significant challenge. Here, such challenge is fulfilled for the first time, by preparation of a flexible and stretchable electrochemical sensor and its incorporation into a microfluidic vascular chip. This allows simulating of in vivo physiological and biomechanical parameters of blood vessels, and simultaneously monitoring the mechanically induced biochemical signals in real time. Specifically, the cyclic circumferential stretch that is actually exerted on endothelium but is hard to reproduce in vitro is successfully recapitulated, and nitric oxide signals under normal blood pressure, as well as reactive oxygen species signals under hypertensive states, are well documented. Here, the first integration of a flexible electrochemical sensor into a microfluidic chip is reported, therefore paving a way to evaluate in vitro organs by built‐in flexible sensors. Abstract : The first integration of a flexible electrochemical sensor into a microfluidic vascular chip is reported. This allows simulating of in vivo physiological and biomechanical parameters of blood vessels, and simultaneously monitoring the mechanically‐induced biochemical signals in real time.